2018
DOI: 10.1016/j.ebiom.2018.10.068
|View full text |Cite
|
Sign up to set email alerts
|

Dual-center, dual-platform microRNA profiling identifies potential plasma biomarkers of adult temporal lobe epilepsy

Abstract: BackgroundThere are no blood-based molecular biomarkers of temporal lobe epilepsy (TLE) to support clinical diagnosis. MicroRNAs are short noncoding RNAs with strong biomarker potential due to their cell-specific expression, mechanistic links to brain excitability, and stable detection in biofluids. Altered levels of circulating microRNAs have been reported in human epilepsy, but most studies collected samples from one clinical site, used a single profiling platform or conducted minimal validation.MethodUsing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
107
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 94 publications
(118 citation statements)
references
References 66 publications
(167 reference statements)
1
107
0
2
Order By: Relevance
“…They were first profiled in human plasma, serum and microvescicles in 2008 [13][14][15] and since then, subsequent studies have found that their levels in peripheral biofluids often fluctuate in patients with various types of cancer, neurological disorders, sepsis, liver and cardiovascular disease (reviewed in [16][17][18]). As such miRNAs have received much interest as potential biomarkers and contain many characteristics which render them ideal biomarker candidates: they are more stable than mRNA as they are resistant to RNase cleavage [19]; expression profiles of miRNAs are often more informative and discriminatory than mRNA profiles; they are abundant and profiling miRNAs is rapid and economical [20]; and their levels often change more rapidly in response to an insult or pathophysiological processes allowing early detection of disease which is critical for progressive illnesses such as cancer, Alzheimer's disease, epilepsy and early life insults [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…They were first profiled in human plasma, serum and microvescicles in 2008 [13][14][15] and since then, subsequent studies have found that their levels in peripheral biofluids often fluctuate in patients with various types of cancer, neurological disorders, sepsis, liver and cardiovascular disease (reviewed in [16][17][18]). As such miRNAs have received much interest as potential biomarkers and contain many characteristics which render them ideal biomarker candidates: they are more stable than mRNA as they are resistant to RNase cleavage [19]; expression profiles of miRNAs are often more informative and discriminatory than mRNA profiles; they are abundant and profiling miRNAs is rapid and economical [20]; and their levels often change more rapidly in response to an insult or pathophysiological processes allowing early detection of disease which is critical for progressive illnesses such as cancer, Alzheimer's disease, epilepsy and early life insults [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous authors have investigated this opportunity in various medical fields. Evidence suggests that they could play an essential role as biomarkers in cancer through exosome-mediated intercellular communication [1,4,[52][53][54], in neurology for the diagnosis and prognosis of Alzheimer's disease [55], for patients with spinal cord injury [56], epilepsy [57] or neurodegenerative ailments [58]. It could also be used in other fields like cardiology, as a faster and more accurate means of diagnosis for acute cardiovascular disease or heart failure [59][60][61] and in the case of infectious diseases for the diagnosis of sepsis [62].…”
mentioning
confidence: 99%
“…For miRNA target identification and Gene Ontology (GO) enrichment analysis, experimentally validated targets were retrieved from miRTarBase Release 7.0 (Chou et al, 2018), TarBase v.8 (Karagkouni et al, 2018), and miRecords (Xiao et al, 2009) while predicted targets were retrieved from TargetScan Release 7.2 (Agarwal et al, 2015) and miRDB Version 6.0 (Liu and Wang, 2019). We calculated a miRNA-target interaction (MTI) score based on combined prediction algorithm scores and the number of publications associated with the validated MTIs, as described previously (Raoof et al, 2018). Enrichment analysis of GO terms was performed on all MTIs with a score >0.1 using ReactomePA R/Bioconductor package (Yu and He, 2016).…”
Section: Rna-sequencing Data Processing and Analysismentioning
confidence: 99%